Pengaruh Likuiditas, Leverage dan Profitabilitas terhadap Nilai Perusahaan pada Sektor Barang dan Konsumsi yang Terdaftar di Bursa Efek Indonesia Periode 2015-2018 - Putriana Panjaitan; Silvina Amanda; Cristin Liviani (Jurnal Ilmiah Universitas Batanghari Jambi, 2020)
The purpose of this study is to analyze and observe the effect of Liquidity, Leverage, and Profitability on Firm Value in the Goods and Consumption Sector listed on the Indonesia Stock Exchange in the 2015-2018 period. This research uses quantitative methods with descriptive types. The research population is the Goods and Consumption Sector which is listed on the Indonesia Stock Exchange for the 2015-2018 period as many as 50 companies. Taking while using purposive sampling and samples obtained 92 samples from 23 sectors of goods and consumption multiplied by 4 years. This method uses the Multiple Linear Regression method. The results obtained from the R Square coefficient test are 9.7%, which means that the variation in the Firm Value variable is described by the independent variable 90.3%. The research results simultaneously show that liquidity, leverage, and profitability have no effect on firm value. Meanwhile, partially shows that liquidity and profitability have no and insignificant effect on firm value, however, the leverage variable has a significant effect on firm value.